Heterocycle–Heterocycle Strategy for 4,5-Disubstituted Pyrrolidine 2,3-Diones: Reductive Rearrangement Approach from Isoxazole Esters - Kamath, Prashantha; Jadhav, Vaibhav; Lal, Mukul (Synlett, 2021)
The work demonstrates the heterocycle–heterocycle interconversion strategy to access 4,5-disubstituted 3-hydroxy-2-pyrrolidinone in moderate to good yields (50–80%). The approach has a distinct advantage over a multicomponent reaction approach as it allows access to unsubstituted 3-hydroxy-2-pyrrolidinone at the nitrogen position for further functionalization.
Keywords: isoxazoles; pyrrolidinones; reductive rearrangement; heterocyle–heterocyle strategy; (3+2) cycloaddition; MCR